2023
DOI: 10.3389/fcimb.2023.1125809
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intravesical Bacillus Calmette-Guérin and chemotherapy on the bladder microbiome in patients with non-muscle invasive bladder cancer

Abstract: IntroductionIntravesical therapy (IVT), including Bacillus Calmette-Guérin (BCG), is the standard of care for high grade (HG) non-muscle invasive bladder cancer (NMIBC). Despite the use of IVT, many patients recur after treatment. The bladder microbiome and its role in disease processes has recently risen to prominence. We aim to characterize changes that occur in the bladder microbiome over the course of intravesical therapy and assess whether these changes correlate with outcomes in patients with NMIBC.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Cumulative studies have suggested that dysbiosis of urobiome influences the microenvironments of the urinary tract and thereby contributing to the onset and progression of the bladder cancer and prostate cancer ( Alfano et al., 2016 ; Annels et al., 2020 ; Chipollini et al., 2020 ; Cai et al., 2021 ; James et al., 2023 ). Urobiome dysbiosis has also been found to affect the treatment response to the bladder cancer ( Annels et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative studies have suggested that dysbiosis of urobiome influences the microenvironments of the urinary tract and thereby contributing to the onset and progression of the bladder cancer and prostate cancer ( Alfano et al., 2016 ; Annels et al., 2020 ; Chipollini et al., 2020 ; Cai et al., 2021 ; James et al., 2023 ). Urobiome dysbiosis has also been found to affect the treatment response to the bladder cancer ( Annels et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the genera most informative for HGSC in the lasso multivariate analysis and in the correlation with significant genomic SNVs, Escherichia/Shigella , Pantoea , and Ralstonia , have been associated with other types of cancer, including bladder, pancreatic, cholangiocarcinoma, colorectal, breast, and oral malignancies [ 42 , 43 , 44 , 45 , 46 ]. Likewise, variants of the dynein axonemal heavy chain ( DNAH ) family have been previously associated with breast and ovarian cancer [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…An investigation involving patients with NMIBC has found that non-recurrence patients tend to exhibit higher levels of Escherichia/Shigella and Ureaplasma, while patients experiencing a relapse after BCG or intravesical therapy tend to exhibit higher levels of Aerococcus, thus being predictive of a poor cancer response [177].…”
Section: Microbiome and Bcg Responsivenessmentioning
confidence: 99%